2005
DOI: 10.1007/s11255-005-0919-4
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Importance of E-cadherin and p53 Gene Expression in Transitional Bladder Carcinoma Patients

Abstract: Significant differences can be helpful to investigate patients more detailed pathologically. These expression rates in different type of transitional cell carcinoma patients may represent a biologically more aggressive cancer, requiring early definitive therapy. This hypothesis should be evaluated in larger studies and prospective clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Among E-CAD mRNA negative patients, 2 were pTa (2 G3), 3 pT1 G3, 1 pT2 G3, 9 pT3 G3 and 2 pT4 G3. These findings are in line with data from the literature (12,13,24). All samples of normal-appearing mucosa distant from superficial bladder tumors were positive on E-CAD analysis, while among the 14 invasive tumors, 11 were negative and 3 were positive.…”
Section: Molecular Findingssupporting
confidence: 91%
“…Among E-CAD mRNA negative patients, 2 were pTa (2 G3), 3 pT1 G3, 1 pT2 G3, 9 pT3 G3 and 2 pT4 G3. These findings are in line with data from the literature (12,13,24). All samples of normal-appearing mucosa distant from superficial bladder tumors were positive on E-CAD analysis, while among the 14 invasive tumors, 11 were negative and 3 were positive.…”
Section: Molecular Findingssupporting
confidence: 91%
“…p53 expression showed no correlation with recurrence rate after BCG treatment in none of the studies [1833]. Although higher protein expression seems to be associated with reduced time to recurrence [23, 34, 35] or progression [18, 19, 23, 26, 32, 34], but this association could not be demonstrated by several other authors (Table 1) [22, 2426, 28, 30, 31]. Only Saint et al (2004) [23] and Lee (1997) [35] found that p53 could be an independent prognostic factor, but with opposite results.…”
Section: Resultsmentioning
confidence: 91%
“…Most studies have associated tissue E-cadherin expression loss with UC recurrence/progression. [47][48][49][50][51][52][53][54][55][56][57][58][59][60] A higher plasma sE-cad level has been associated with bladder cancer in comparison with healthy controls; a higher preoperative plasma sEcad level has been associated with nodal metastases and shorter PFS in patients treated with radical cystectomy. 61 Our findings are exploratory, and the role of sE-cad in UC merits further investigation.…”
Section: Discussionmentioning
confidence: 99%